Finite element analysis of temperature dependence of the piezoresistance of silicon - Wang, Zhao. (2013)
There is a widespread demand for high-temperature pressure sensors at temperatures above 200 °C and with high-frequency responses. PZT based devices owing to its excellent electrical and mechanical properties at rash environments, is a great candidate for use as an electromechanical sensor for high-temperature applications. Termally shear stress increases with temperature incease within 30~ 100°C range. This project characterized Gage factor, resonant frequency and deformation of the microfabricated PZT structure in interaction high temperature ambient under continuous stress and applying dynamic forces. The corresponding impedance and resonant frequency were tested by Agilent 4294A impedance analyzer, and thus Q factor can be calculated from the impedance measurements. The results of the study showed the dramatic decline of resonant frequency around 80°C can be related to the phase change from rhombohedral to tetragonal. The variations of the resonant frequency from 80°C to 390°C might be related to the lattice parameter changes because phase change to cubic has not arisen.